Effect of 5E Based Instructional Approach on Achievement and Interest in Social Studies among Grade IX Students - Gupta, Rupa; Singh, Vikramjit; Gangmei, Elizabeth (JOURNAL OF INDIAN EDUCATION, 2022)
The 5E (Engage, Explore, Explain, Elaborate, and Evaluate) is an instructional model which provides a framework for a constructivist, guided inquiry approach and enables the learners to create or invent different ideas over the conventional one. The study focuses on the effect of the 5E based instructional approach on the achievement and interest in social studies among Grade IX students. The specific design used here was Pre-test or Post-test equivalent group design with the self-constructed and validated tools. The findings of the study revealed that there is a significant effect of the 5E based instructional approach on the interest and achievement in social studies between girls less than 14 years and 14 and above years of age of Grade IX learning through a 5E based instructional approach.